Perancangan Sistem Informasi Belanja Online Pada Toko Sembako Ajan Sambas Berbasis Website (Indonesian Journal of Technology and Computer Science, 2025)
This research discusses the design of an online shopping information system for Toko Sembako Ajan Sambas based on a website, aiming to simplify the process of purchasing daily necessities for customers and assist administrators in efficiently managing product and transaction data. The system was developed using the prototype method and modeled with a use case diagram to illustrate user interactions with the system. The user interface was designed to be simple, informative, and user-friendly, featuring a main page with “Home,” “About,” and “Products” navigation, a product page displaying available items with purchase buttons, a shopping cart page, a purchase history page, and a payment confirmation page. Additionally, an admin page was created with a structured dashboard layout for managing product, transaction, and customer data. The results of this study indicate that the designed system provides users with a convenient, fast, and efficient online shopping experience while supporting better data management for the store’s administrators.
Keywords: Online Shopping; Website; Prototype; Groceries